2018
DOI: 10.21161/mjm.114517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 2,2-DCP degrading bacteria isolated from a paddy field at a rural area in Malang, Indonesia

Abstract: Aims: The use of herbicide effectively controls weeds in agricultural practice. However, its release to the surrounding surface water bodies may lead to environmental issues. The aim of this study was to isolate the bacteria that were able to remove 2,2-dichloropropionic acid (2,2-DCP) from a paddy field located in Malang. Methodology and results: The 2,2-DCP degrading bacteria were isolated and their ability to grow on higher 2,2-DCP concentrations (50 and 80 mM) was tested. Bacterial degradation of 2,2-DCP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Similar observation was seen in other studies as reported earlier [42,43]. Chloride ions released into the growth medium was due to the hydrolysis of 2,2-DCP inside the cells resulted in chloride ion released outside the cells [42,43] [ 44,45]. The product of 2,2-DCP dehalogenation resulted in pyruvate, that was essential for cell growth.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar observation was seen in other studies as reported earlier [42,43]. Chloride ions released into the growth medium was due to the hydrolysis of 2,2-DCP inside the cells resulted in chloride ion released outside the cells [42,43] [ 44,45]. The product of 2,2-DCP dehalogenation resulted in pyruvate, that was essential for cell growth.…”
Section: Discussionsupporting
confidence: 85%
“…Pyruvate was further catabolized to supply carbon and energy required by cells to grow. Therefore, the high concentration of released chloride ion may indicate the high demand of pyruvate as required for a rapid growth [45]. The tolerance to the high concentration of 2,2-DCP may be related to frequent exposure of the organic halide at the sampling location especially in the presence of naturally occurring halogenated compound [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarised the maximum growth of strain ZT in each 2,2-DCP concentration. Strain ZT showed good growth condition at 10 mM, 20 mM and 30 mM of 2,2-DCP, whereas another study showed that Acinetobacter calcoaceticus strain BB9.2 and Pseudomonas plecoglossicida strain BC14.3 could grow well in the media containing up to 50 mM and 80 mM of 2,2-DCP (Mulyawati et al, 2018). Most of the previously reported cases showed that 2,2-DCP above 30 mM was toxic to the cells (Oyewusi et al, 2020, Ismail et al, 2017, Muslem et al, 2017, Heidarrezaei et al, 2020.…”
Section: Analysis Of Growth In Liquid 22-dcp Minimal Mediummentioning
confidence: 94%